Knowledge of oral cancer risk factors amongst high‐risk Australians: findings from the LESIONS programme. (December 2016) - Dost, F; Do, L; Farah, CS
Abstract: Background: Patient awareness of risk factors associated with cancer has been shown to increase patient presentation for screening and early detection. This study aimed to identify the level of awareness of oral cancer risk factors in a high risk Australian population. Methods: Participants were recruited from the LESIONS programme between April 2012 and April 2014. Demographics were collected via semi‐structured interview. A self‐administered questionnaire was provided, listing a number of possible oral cancer risk factors. Participants were requested to indicate their level of agreement on a three‐point scale. Bivariate and multivariable analysis was performed. Results: A total of 1498 participants took part in the LESIONS programme and were invited to complete the questionnaire. The most common risk factors thought to be associated with oral cancer were smoking (87.5%), poor oral hygiene (67.9%) and family history (61.1%). Only 50.2% of respondents were aware of alcohol consumption as a risk factor. Conclusions: While most participants were aware of the association between smoking and oral cancer, only half were aware of the significant risk alcohol consumption poses. A significant portion of participants also held a number of inaccurate beliefs in relation to oral cancer risk. These findings can benefit both clinicians and public health policy makers in targeting oral cancer education.